2021
DOI: 10.3389/fpsyt.2021.575837
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effects of a Multimodal Inpatient CBASP Program: Rate of Occurrence and Their Impact on Treatment Outcome in Chronic and Treatment-Resistant Depression

Abstract: Background: A growing number of studies indicate that the Cognitive Behavioral Analysis System of Psychotherapy (CBASP) is effective in treating chronic depression. However, there is no systematic research into possible negative effects. Therefore, the objectives of the study were to investigate the rate of occurrence of negative effects of an inpatient CBASP program and their impact on treatment response.Methods: Patients with chronic depression and treatment resistance who completed the 12-week multimodal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…The most common negative effect was periods of feeling bad (31.2% and 30.2%, respectively). In an inpatient CBASP treatment for chronic depression, 92.3% of patients reported at least one negative effect, with the most common negative effect being feelings of dependence on the therapist (45.2%) ( 10 ). In a DBT-oriented psychiatric day hospital for patients with borderline syndrome, 97.6% of the patients reported at least one negative effect with the most prevalent effect of longer periods of feeling bad (97.6%) ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common negative effect was periods of feeling bad (31.2% and 30.2%, respectively). In an inpatient CBASP treatment for chronic depression, 92.3% of patients reported at least one negative effect, with the most common negative effect being feelings of dependence on the therapist (45.2%) ( 10 ). In a DBT-oriented psychiatric day hospital for patients with borderline syndrome, 97.6% of the patients reported at least one negative effect with the most prevalent effect of longer periods of feeling bad (97.6%) ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Inventory for the Assessment of Negative Effects of Psychotherapy (INEP; 7) is a questionnaire that assesses negative effects of psychotherapy, as defined above, as well as therapeutic malpractice from the patient's perspective. It is practical and has been used in several studies with patients with mental health disorders (7)(8)(9)(10)(11). In these studies, between 58.7% and 97.6% of the patients reported at least one negative effect, such as having difficulty making important decisions without their therapist, having more downs around the end of therapy, or feeling hurt by the therapist's statements.…”
Section: Introductionmentioning
confidence: 99%
“…Side effects as measured with the INEP have been linked to poorer therapeutic alliance (measured with the Helping Alliance Questionnaire), more interpersonal difficulties (measured with the Inventory of Interpersonal Problems, Gerke, Meyrose, Ladwig, Rief, & Nestoriuc, 2020), higher treatment expectations (Abeling, Müller, Stephan, Pollmann, & De Zwaan, 2018;Rheker, Beisel, Kräling, & Rief, 2017) and lower treatment satisfaction (Ladwig et al, 2014). Treatment response, on the other hand, is not generally reduced if side effects are present (Herzog, Häusler, Normann, & Brakemeier, 2021). Two studies using the INEP found side effects in 15-20% of mixed outpatient CBT samples in university clinics (Gerke et al, 2020;Nestoriuc & Rief, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…There is also increasing interest in determining specific negative effects of a given psychotherapy. For instance, patients with chronic depression and treatment resistance who received Cognitive Behavioral Analysis System of Psychotherapy (CBASP) reported negative effects of up to 92.3% and dependence on their therapist of 45.2% (Herzog et al., 2021 ). The lack of standardized definitions and effective evaluation tools may be the main reasons that the side effects of psychotherapy have not been fully studied (Herzog et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%